INCLUSIVE CHARGED-PARTICLE PRODUCTION NEAR THE KINEMATIC LIMIT IN E+E- ANNIHILATION AT 29 GEV - Derrick, M; Kooijman, P; Loos, J; Musgrave, B; Price, L; Schlereth, J; Sugano, K; Weiss, J; Wood, D; Baringer, P; Blockus, D; Brabson, B; et al. (1985)
Inclusive production of charged particles has been studied in e+e- annihilation at ss=29 GeV using the high resolution spectrometer at PEP. Differential cross sections are presented in the range of scaled energy 0.1